Monetary and banking policy: paper presented at the Conference on National Reconstruction and Development in Nigeria in Ibadan, March, 1969. - Ekukinam, A. E.; Nigerian Institute of Social and Economic Research (Ibadan : Nigerian Institute of Social and Economic Research, 1969)
This is a paper presented at the Conference on National Reconstruction and Development in Nigeria in Ibadan, March, 1969."The conference was organised by the Federal Ministry of Economic Development, Lagos, and the Nigerian Institute of Social and Economic Research, Ibadan." It further highlights some of the common produce including their effects and contribution to the national development. The conference covered issues like: economic and social survey; federalism, economic planning and plan administration; wages costs and prices; fiscal measures; energy resources and utilization; monetary and banking policy; health, housing and social welfare
asm 06/03/2019
Loans
Keywords: Economic policy; Social conditions; Economic history; Social policy; Nigeria